Behaviour of starch exposed to microwave radiation treatment. Issue 1 (18th March 2013) - Braşoveanu, Mirela; Nemţanu, Monica R.; Tester, Richard F.
Abstract This work is an overview of the literature in the area of microwave treatment of starch strongly related to changes in its physicochemical, functional and structural properties. The importance of good knowledge of the microwave parameters and starch dielectric properties is highlighted to avoid the improper microwave application on starch or starch‐based materials. Future perspectives of microwave processing of starch are suggested.